The genus Houssayanthus (Sapindaceae) in Mexico - Rzedowski, Jerzy; Calderón de Rzedowski, Graciela (Instituto de Ecología, A.C., 2006)
Two Mexican species of the family Sapindaceae are best placed in the genus Houssayanthus, originally proposed by Hunziker for a group of South American plants bearing vegetative characters and fruits of structure and consistence similar to those of Serjania, but with central locules, as in the fruits of Urvillea. Houssayanthus serjanioides, described as a new species, is a predominantly herbaceous prostrate or scandent plant, inhabiting preferably oak forests in the northeastern part of the state of Queretaro and in the Guadalcazar region of the state of San Luis Potosi. Urvillea biternata Weatherby, a species known only from the state of Guerrero and described in absence of mature fruits, is also transferred to Houssayanthus. Both Mexican species differ from the South American ones in their essentially biternate (not 3-foliolate or pinnate) leaves and in their embryos with unequal and slightly curved (not subequal and more or less straight) cotyledons. A historical summary of the knowledge of Houssayanthus is presented, as well as an emended description of the genus and a key to separate the five known species, emphasizing the apparent lack of close relationship between several of them.